The environment qualities evaluation of a degraded area in recuperation and the drying process of a Brazilian soil using nonconventional methods at micrometric scale - Tseng, Chien Ling (2017)
Soil is a fundamental resource in the environment, its sustainable use is vital to food supply and, consequently, life continuity on the Earth. However, the currently status of this resource in the world is critical and, therefore, the need of soil recovery measures and methods to evaluate it is urgent. The aim of this study is to provide a holistic evaluation about soil architecture at different recovery states, as well as its interaction with fluid in the environment by using nonconventional methods. It was organized a tool package that allows to analyze soil physical at geometric, morphometric and energy scope, to show in a more efficient way, which physical parameters indicate the physical and environmental quality. Subsequently, this package was applied to the study of six types of managements in different stages of development by using of physical parameter derived from the package; It was also analyzed the efficiency of recovery techniques under different perspectives. In addition, the soil-water dynamic was evaluated in a particular condition by using the same tools, offering knowledge about this interaction in the environment along the time. Finally, it is expected that this work can bring new insight on preservation and recovery of this environmental resource.